1989
DOI: 10.1104/pp.89.4.1331
|View full text |Cite
|
Sign up to set email alerts
|

31P-Nuclear Magnetic Resonance Determination of Phosphate Compartmentation in Leaves of Reproductive Soybeans (Glycine max L.) as Affected by Phosphate Nutrition

Abstract: Most leaf phosphorus is remobilized to the seed during reproductive development in soybean. We determined, using (31)P-NMR, the effect phosphorus remobilization has on vacuolar inorganic phosphate pool size in soybean (Glycine max [L.] Merr.) leaves with respect to phosphorus nutrition and plant development. Phosphate compartmentation between cytoplasmic and vacuolar pools was observed and followed in intact tissue grown hydroponically, at the R2, R4, and R6 growth stages. As phosphorus in the nutrient solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0
5

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 25 publications
(30 reference statements)
6
69
0
5
Order By: Relevance
“…In our experiment, growth independent P consumption was observed in the P free-access treatments. This can be attributed to the accumulation of inorganic phosphorus (Pi) in the vacuole [32,46] and to a higher concentration of P incorporated in organic compounds in the cell as polyphosphate or phytate [13]. This ability may be ecologically important in enabling plants to face seasonal variations in phosphorus availability observed in the field [10].…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, growth independent P consumption was observed in the P free-access treatments. This can be attributed to the accumulation of inorganic phosphorus (Pi) in the vacuole [32,46] and to a higher concentration of P incorporated in organic compounds in the cell as polyphosphate or phytate [13]. This ability may be ecologically important in enabling plants to face seasonal variations in phosphorus availability observed in the field [10].…”
Section: Discussionmentioning
confidence: 99%
“…This could be because of increased cytokinins synthesis (Horgan and Wareing, 1980) and supply of photosynthates (Marschner, 2012) for flower formation. Perhaps, P deficiency has been related to the reduction in foliar expansion (Fredeen et al, 1989), decrease in the number of leaves (Lynch et al, 1991) and loss in photosynthetic efficiency (Lauer et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…P-NMR studies have revealed that plant cells selectively distribute Pi between cytoplasmic ("metabolic") and vacuolar ("storage") pools, with cytoplasmic Pi being maintained essentially constant at the expense of large fluctuations in vacuolar Pi (Lauer et al, 1989). With prolonged Pi-deprivation, however, vacuolar Pi stores become exhausted, and this is followed by considerable reductions in cytoplasmic Pi (Lauer et al, 1989).…”
Section: Effect Of Pi Nutrltlon On the Pi Nucleotide-p And Ppi Poolmentioning
confidence: 99%
“…At the metabolic level, much attention has been devoted to the effect of Pi status on the secretion of acid phosphatases, Pi uptake rates, and other mechanisms that may serve to increase the availability of Pi to Pi-deprived cells (Goldstein et al, 1989;Lefebvre et al, 1990;Duff et al, 1991aDuff et al, , 1991b. The effects of Pi nutrition on the rates of photosynthesis and photosynthate partitioning in leaves have also been well documented (Thorsteinsson and Tillberg, 1987;Lauer et al, 1989;Fredeen et al, 1990). By contrast, investigations of the metabolic adaptations of plant respiratory pathways to Pi deficiency have been limited.…”
mentioning
confidence: 99%